A Resurgent East Asia : Navigating a Changing World - Mason, Andrew D. (Washington, DC: World Bank, 2018)
East Asia has been a paragon of global development success. The dramatic transformation of the region over the past half century—with a succession of countries having progressed from low-income to middle-income and even to high-income status—has been built on what has come to be known as the “East Asian development model.” A combination of policies that fostered outward-oriented, labor-intensive growth while strengthening basic human capital and providing sound economic governance has been instrumental in moving hundreds of millions of people out of poverty and into economic security. Yet East Asia’s economic resurgence remains incomplete. More than 90 percent of its people now live in 10 middle-income countries, many of which can realistically aspire to high-income status in the next generation or two. But these countries are still much less affluent and productive than their high-income counterparts. Even as the region’s middle-income countries attempt to move up to high-income status, they confront a rapidly changing global and regional economic environment. Slowing growth in global trade and shifts in its patterns, rapid technological change, and evolving country circumstances all present challenges to sustaining productivity growth, fostering inclusion, and enhancing state effectiveness. A Resurgent East Asia: Navigating a Changing World is about how policy makers across developing East Asia will need to adapt their development model to effectively address these challenges in the coming decade and sustain the region’s remarkable development performance.